Spectral Evolution in Blazars : The Case of CTA 102 - Fromm, Christian (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2015)
This prize-winning thesis deals with the observation and modeling of the spectral evolution of blazars. Based on single-dish light curves, a model of shock-shock interaction is tested and confirmed using multi-frequency high resolution Very Long Baseline Observations. He presents state-of-the art numerical relativistic hydrodynamic simulations and the corresponding non-thermal emission is calculated (eRHD simulations). The author further presents new analysis techniques for VLBI observations that can be applied to numerous sources and provide reliable results including an error estimate using Monte Carlo simulations. He also develops an analytical shock model that can be applied quickly to other single dish observations. He shows how novel techniques of extraction of physical parameters from observations can be applied to other astrophysical sources and provide a link to a better understanding of the physical mechanism operating in blazar jets.